The pan‐Bcl‐2 blocker obatoclax promotes the expression of Puma, Noxa, and Bim mRNA and induces apoptosis in neoplastic mast cells. Issue 1 (19th September 2013) - Peter, Barbara; Cerny‐Reiterer, Sabine; Hadzijusufovic, Emir; Schuch, Karina; Stefanzl, Gabriele; Eisenwort, Gregor; Gleixner, Karoline V.; Hoermann, Gregor; Mayerhofer, Matthias; Kundi, Michael; Baumgartner, Sigrid; Sperr, Wolfgang R.; et al.
Abstract : Obatoclax exerts profound antineoplastic effects on malignant mast cells in advanced systemic mastocytosis, and shows synergistic growth‐inhibitory effects when combined with other targeted drugs. Abstract : Advanced SM is an incurable neoplasm with short survival time. So far, no effective therapy is available for these patients. We and others have shown recently that neoplastic MC in ASM and MCL express antiapoptotic Mcl‐1, Bcl‐2, and Bcl‐xL. In this study, we examined the effects of the pan‐Bcl‐2 family blocker obatoclax (GX015‐070) on primary neoplastic MC, the human MC leukemia cell line HMC‐1, and the canine mastocytoma cell line C2. Obatoclax was found to inhibit proliferation in primary human neoplastic MC (IC50 : 0.057 μM), in HMC‐1.2 cells expressing KIT D816V (IC50 : 0.72 μM), and in HMC‐1.1 cells lacking KIT D816V (IC50 : 0.09 μM), as well as in C2 cells (IC50 : 0.74 μM). The growth‐inhibitory effects of obatoclax in HMC‐1 cells were accompanied by an increase in expression of Puma, Noxa, and Bim mRNA, as well as by apoptosis, as evidenced by microscopy, TUNEL assay, and caspase cleavage. Viral‐mediated overexpression of Mcl‐1, Bcl‐xL, or Bcl‐2 in HMC‐1 cells was found to introduce partial resistance against apoptosis‐inducing effects of obatoclax. We were also able to show that obatoclax synergizes with several other antineoplastic drugs, including dasatinib, midostaurin, and bortezomib, in producing apoptosis and/or growth arrest in neoplastic MC. Together, obatoclax exerts major growth‐inhibitory effects on neoplastic MC and potentiates the antineoplastic activity of other targeted drugs. Whether these drug effects can be translated to application in patients with advanced SM remains to be determined.